Trio-ethnographic Reflection on Using Digital Storytelling to Enhance Learners’ Engagement (Journal of Contemporary Educational Policies and Practices, 2025)
The teaching and learning process in the digital landscape is evolving beyond traditional one-way knowledge delivery. Using trio-ethnography, a combination of duoethnography and photography (Le et al., 2021), we sought to explore how to integrate digital storytelling (DST) into teaching and learning processes to engage learners. Central to our paper are our narratives via three lenses: educators, learners, and a storytelling expert. In the three circles of the indigenous approach (Lavallée, 2009), we share our narrative inquiries. The sharing circles were a mixture of offline meetings, our co-emerging conversations in verbal format, and online meetings to clarify the written format of our dialogues. Three themes emerged: elements of digital storytelling, peer-to-peer learning, and level of engagement. We found that educators are not the primary source for integrating digital tools. Inquiry-based peer to peer learning (P2PL) determines the efficacy of learners’ meaning-making and engagement. Aiming for explicit learning outcomes, educators would flexibly modify activities for diverse learning styles. In addition, empathy is the catalyst for lecturer-student intellectual relationships, enabling appropriate learner-experience design approaches. Furthermore, we hope to contribute to the trio-ethnographic methodology by using visual communication through sharing circles to articulate our meaning-making and illustrate our trusted connections.
Keywords: Trio-ethnography; digital storytelling; peer-to-peer learning; engagement; teaching and learning